Evaluation of the university students' attitudes about drug/medicinal product utilization [Üni̇versi̇te öǧrenci̇leri̇ni̇n i̇laç/tibbi̇ ürün kullanimina yöneli̇k tutumlarinin deǧerlendi̇rmesi̇] - (:unkn) unknown (My University, 2010)
Objective: A new set of developments take place every day in the process of marketing-utilization of drugs/medical products (DMP). It must be known how the consumers approach to them. It was aimed to investigate the observation of students' attitudes regarding utilization of DMP. Methods: Data were obtained with a questionnaire applied to 205 university students. The details of their attitudes toward the sale of DMP and some of their habits related to the utilization of these products were questioned. Results: The influence ratio of students from advertisements while buying nonprescribed DMP was 11.4%. Most of them were against DMP advertisments aired on TVs and non-TV mass media (70.4% and 64.7% respectively). Their average satisfaction degree of service from the pharmacy was 73% and both the most and least satisfying service was "drug information" (36.0% and 19.5% respectively). Students (especially pharmacy students) were against "pharmacy chains" (59.4%). Conclusion: University students support the continuing of a pharmacy-focused service concerning the consumption of DMP, but disapprove the advertising. Similar researches should also be done for other groups in the society. It would be useful if all these observations were considered in the process of a new organization of the DMP service to consumers.
Keywords: Drug/medicinal product advertising; Drug/medicinal product sales; Pharmacy chain; University students